Pré-tratamento da biomassa do coco usando líquidos iônicos próticos para produção de nanocelulose e posterior aplicação como estabilizante de emulsões - Ferreira, Priscilla Fernanda de Oliveira (2021)
Lignocellulosic materials are promising sources of energy and biomaterials. In this context, the biomass from the mesocarp of coconut, which would naturally be a food residue, can be used to produce nanocellulose. For that, this work proposed approaches for pre-treatment of coconut biomass using protic ionic liquids (PIL's), solvents that have specific characteristics and less impact from the environmental point of view, followed by acid hydrolysis, to obtain nanocellulose suspensions. Thus, three PIL's 2-hydroxy-ethylammonium acetate (2-HEAA), N-methyl-2-hydroxy-ethylammonium acetate (M-2HEAA) and 2-hydroxy-diethylammonium acetate (HDEAA)) were produced in the laboratory and characterized by physicochemical properties, Fourier Transform Infrared Analysis (FTIR) and Nuclear Magnetic Resonance spectroscopy (NMR). Two pretreatment methodologies were adopted: Methodology A - biomass treatment with PIL's in a reactor in a proportion of 10% (m/m) at 130ºC, 350 rpm, 6h, followed by treatment with 2% sodium hydroxide (80ºC, 2h); Methodology B – the order of methodology A was inverted and the temperature adopted was 150ºC. After that, the biomasses were characterized by chemical composition, FTIR, Scanning Electron Microscopy (SEM) and Thermogravimetric Analysis (TGA). Afterwards, the biomasses treated in the mentioned methodologies were submitted to acid hydrolysis, using sulfuric acid 64% (m/m) in the proportion of 1:10 (g/ml) at 45 ºC, for 3 hours. At the end of hydrolysis, the nanocellulose was neutralized and characterized by zeta potential, particle size and contact angle. The results showed that the ionic liquid 2-HEAA was the most efficient in removing lignin and hemicellulose fractions, which was confirmed by chemical characterization and SEM. When using Methodology B, there was a 17.4% delignification, a 14% reduction in hemicelluloses and a 50.8% gain in cellulose. Furthermore, acid hydrolysis provided a stable nanocellulose suspension (zeta potential of -34.6 mV) with particles in the nanometer scale and more thermally resistant. Finally, the nanocellulose suspension obtained by this methodology was tested as a stabilizer for oil-in-water emulsions, showing satisfactory results using a concentration of 0.50%, which generated a stable emulsion for 14 days (-47.5 mV of zeta potential and average diameter of 6.23 µm).